2013
DOI: 10.1017/s1751731113001316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of detoxified karanja (Pongamia spp.) cake on testicular architecture and semen production in ram lambs

Abstract: The protein-rich non-conventional detoxified karanja cake (dKC) can be used in place of conventional protein supplements like soybean meal (SBM), groundnut meal, etc. in livestock feed. The present study was conducted to assess the effect of two levels of dKC by replacing SBM on testicular architecture, semen quality and expressions of mRNAs encoding luteinizing hormone receptor (LHR) and insulin-like growth factor (IGF-I) in testes of ram lambs. Eighteen ram lambs were randomly divided into three groups (n 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
0
6
1
Order By: Relevance
“…Changes like the degeneration of the seminiferous tubules with the presence of a fewer number of spermatogonial cells may affect the reproductive performance when such rams are used in the breeding purpose. Contrary to our finding, Dineshkumar et al. (2013) did not notice any changes in the testicular weight of rams when detoxified karanj cake (DKC) was included at a higher level (18% and 29%) in the concentrate.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Changes like the degeneration of the seminiferous tubules with the presence of a fewer number of spermatogonial cells may affect the reproductive performance when such rams are used in the breeding purpose. Contrary to our finding, Dineshkumar et al. (2013) did not notice any changes in the testicular weight of rams when detoxified karanj cake (DKC) was included at a higher level (18% and 29%) in the concentrate.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the spermatozoa concentration was reduced when DKC was included at 29% in the concentrate. However, the histological section of the testis of lambs fed 18% DKC in the concentrate mixture showed edema in intertubular space with moderate damage to the seminiferous tubular cells ( Dineshkumar et al., 2013 ), while feeding of DKC at higher level (29%) in the same experiment showed severe damage to seminiferous tubular epithelial cells with loss of interstitial cells.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In vitro laboratory Page66 analysis of karanja seed cake has already revealed characteristically high crude protein ~30% (Ravi et al, 2000) and suitable calcium: phosphorus ratio (Soren and Sastry, 2009) compared to soybean meal and cottonseed meal supporting its evaluation as a protein supplement. The karanj seed cake is often blamed for low palatability and poor digestibility due to the presence of various anti nutritional factors such as karanjin (0.132%), tannin (6.55%) and trypsin inhibitors (3.17%) (Panda et al, 2006;Dinesh et al, 2013). However, it was suggested that solvent extracted karanj seed cake (SKC) is safe for animal feeding (Prabhu, 2002, Thakur et al, 2014 and its level of feeding could be further improved through alkali processing of SKC Panda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%